An Error Analysis of EFL Pre-services Teacher’s Academic Writing from Dulay’s Surface Strategy Framework in a Multilingual Context - Irawansyah (Edukasi Lingua Sastra, 2026)
The capacity to write academically is an essential skill for EFL pre‑service teachers in teacher-education programs, as it directly influences the quality of their future classroom practice. However, the continued occurrence of grammatical errors in their scholarly writing reveals difficulties in mastering English grammar, especially within multilingual learning environments. This study aimed to identify and analyze the proportions of grammatical errors present in the academic writing of EFL pre‑service teachers, using Dulay’s surface strategy framework and investigate the implications of the results of the error analysis for teaching academic writing in teacher education programs. A qualitative descriptive design was adopted, involving 25 learners from the English education department. Academic essays written by the learners served as data, and the errors were classified into four groups: omission, addition, misformation, and misordering. Findings showed that misformation errors were the most common (204 items, 40.8 %), followed by omission errors (150 items, 30 %), addition errors (80 items, 16 %), and misordering errors (66 items, 13.2 %). The results indicate that students struggle with grasping grammatical structures and are influenced by their first language (L1) when producing academic writings. Moreover, the study suggests that analyzing grammatical errors can be an effective diagnostic instrument in teacher‑education programs. Accordingly, it is advised that English teacher‑education curricula incorporate feedback grounded in error analysis and explicit grammar instruction within academic writing courses, particularly in multilingual contexts.